Sharia Banking Efficiency in Developing Countries - Muhammad Khoirul Fuddin; Niken Hesty Wulandari; Nur Shabrina Rahmahsari Suyono; Robiatul Adawiah (Jurnal Reksa, 2024)
Several decades ago, the 1998 financial crisis in ASEAN developing countries had a limited impact on the performance of sharia banking due to its adherence to principles of transparency and fairness in its operations, allowing it to sustain growth under various conditions. This study examines the effect of CAR, ROA, and FDR on the efficiency of Islamic banking in developing countries, specifically the United Arab Emirates, Malaysia, Kuwait, and Qatar. Employing quantitative methods and panel data regression analysis, the findings reveal that CAR does not have a significant individual effect on Sharia banking efficiency, whereas FDR and ROA significantly enhance banking efficiency. This research contributes valuable insights into the role of these financial ratios in shaping the efficiency of Islamic banks in developing countries, providing practical implications for policymakers and banking professionals aiming to improve sharia banking performance.